2015
DOI: 10.1021/ar500431g
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Atmospherically-Relevant Chemical Reactions in Water Clusters and on Liquid Water and Ice Surfaces

Abstract: CONSPECTUS: Reactions on water and ice surfaces and in other aqueous media are ubiquitous in the atmosphere, but the microscopic mechanisms of most of these processes are as yet unknown. This Account examines recent progress in atomistic simulations of such reactions and the insights provided into mechanisms and interpretation of experiments. Illustrative examples are discussed. The main computational approaches employed are classical trajectory simulations using interaction potentials derived from quantum che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 52 publications
3
103
0
Order By: Relevance
“…[50][51][52][53][54][55][56] For AIMD simulations modeling a macroscopic 58 When examined with a higher level of theory with optimized geometries, an MP2/SOS-RIMP2/aSVP AIMD study with four waters exhibited a maximum charge separation, obtained via natural population analysis, between the NO and NO 3 moieties of 1.5 a.u. 60 A dynamic B3LYP/6-31G study based on gradients and Hessians indicated that clusters of symmetric N 2 O 4 with 0-7 H 2 O isomerized to the asymmetric ONONO 2 isomer in water assisted as well as non-water assisted pathways and suggested the participation of NO + NO 3 À . expected for an ion pair.…”
Section: Models and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53][54][55][56] For AIMD simulations modeling a macroscopic 58 When examined with a higher level of theory with optimized geometries, an MP2/SOS-RIMP2/aSVP AIMD study with four waters exhibited a maximum charge separation, obtained via natural population analysis, between the NO and NO 3 moieties of 1.5 a.u. 60 A dynamic B3LYP/6-31G study based on gradients and Hessians indicated that clusters of symmetric N 2 O 4 with 0-7 H 2 O isomerized to the asymmetric ONONO 2 isomer in water assisted as well as non-water assisted pathways and suggested the participation of NO + NO 3 À . expected for an ion pair.…”
Section: Models and Methodologymentioning
confidence: 99%
“…Solvent mitigated femtosecond transfer processes reduce the charge to BÀ0.25 a.u. 60 But in contrast to dinitrogen pentoxide, the charge on each fragment is rather constant (except for the vibrational motions) until reaction at 8.7 ps. As the hydronium ion migrates away via proton hopping and the aqueous solvation shell establishes itself, the charge slowly decreases further until solvated Cl À reaches a charge of À0.72 a.u.…”
Section: Charge Distribution For Reactionmentioning
confidence: 99%
“…58 Water plays a vital role in the molecular arrangement at the aqueous surface to advance interfacial reactions. 59,60 Additional 2D PCA results are depicted in Supplementary Fig. 17.…”
Section: Temporal Evolution Of Dark-aging Productsmentioning
confidence: 99%
“…The D layer is the innermost layer of the ionosphere, ranging from 60 to 90 km in altitude, where Lyman series-α hydrogen radiation from the Sun gives rise to abundant nitrosonium ions (NO + ). In addition to the ionospheric reaction between NO + and water, explorations of the chemical reactivity of NO + and water clusters (2-4) have implications for understanding the mechanisms of atmospherically relevant reactions in water clusters (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%